Effectiveness of dual-site transcranial magnetic stimulation on motor function and activities of daily living in stroke patients: a systematic review and meta-analysis of randomized controlled trials - Qin, Jiawei; Hong, Zhenzhen; Wang, Jingfeng; Zhang, Yi; Zhuang, Huihong; Hong, Shanshan; Zheng, Liling (Frontiers in Neurology, 2025)
BackgroundDual-site transcranial magnetic stimulation (TMS) has emerged as a promising neuromodulation technique in stroke rehabilitation. By targeting multiple brain regions, dual-site TMS may enhance neuroplasticity more effectively than single-site stimulation. However, its clinical efficacy remains uncertain.ObjectiveTo systematically evaluate the effects of dual-site TMS in improving motor function and activities of daily living (ADL) in patients with stroke.MethodsWe conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) following PRISMA guidelines. Seven electronic databases were searched from inception to February 19, 2024. Studies comparing dual-site TMS with single-site TMS, sham dual-site TMS, or routine rehabilitation in stroke patients were included. Outcomes included Fugl-Meyer Assessment (FMA), FMA-Upper Limb (FMA-UL), Action Research Arm Test (ARAT), Barthel Index (BI), Modified Barthel Index (MBI), Wolf Motor Function Test (WMFT), and others. Methodological quality was assessed using the PEDro scale. Meta-analyses were performed using a random-effects model.ResultsFourteen RCTs involving 724 participants were included. Dual-site TMS significantly improved upper limb motor function compared with single-site TMS (MD = 7.07, 95% CI: 1.46 to 12.68, p < 0.001) and sham dual-site TMS (MD = 14.45, 95% CI: 6.23 to 22.66, p < 0.001). ADL outcomes also favored dual-site TMS over single-site TMS (MD = 9.90, 95% CI: 7.82 to 11.98, p < 0.001) and sham dual-site TMS (MD = 21.13, 95% CI: 9.37 to 32.88, p < 0.001). Subgroup analyses suggested enhanced benefits in subacute phase stroke and in protocols with >20 sessions. Sensitivity analysis confirmed robustness of findings. No serious adverse events were reported.ConclusionDual-site TMS combined with routine rehabilitation is more effective than single-site TMS or sham dual-site TMS in improving motor function and ADL among stroke patients. These findings support its clinical application as an adjunct to conventional therapy. Further high-quality trials are needed to optimize stimulation protocols and confirm long-term effects.